Correlation between gingival thickness and occurrence of gingival recession - Pradeep Koppolu; Asal Abdulrahman Al Arabi; Mira Jameel Al Khayri; Fatimah Ali Alfaraj; Wala Mohammed Alsafwani; Sara Fahad Alhozaimi; Yara Jameel Alrashidi (Wolters Kluwer Medknow Publications, 2023)
Background: Gingival recession (GR) has become a common problem among patients. GR is associated with increased accumulation of plaque, root caries, abrasion and cervical wear, and dentinal hypersensitivity. The present study aimed to examine the correlation between gingival biotypes and the occurrence of GR. Methods: The study initially recruited 94 subjects; however, 54 of them did not have any recession sites, and hence were discarded. Therefore, the analysis was performed on 40 subjects. The study particularly compared the relationship between the recession length (RL) and width along with the gingival thickness (GT). As such, different clinical parameters were analyzed, namely, RL, recession width (RW), keratinized gingival width (KGW), and GT. Results: Based on the statistical analysis (descriptive statistics and Pearson's correlation) conducted on the collected data, the study established that the gingival RL has a significant negative relationship with GT, which implied that the amount of thickness is inversely proportional to the RL. The study also found a significant positive correlation between RW and RL as well as between GT and KGW. Conclusion: Based on the findings, the study thus concluded that the gingival biotype (thickness) significantly determines the occurrence and extent of GR.